Developing historical and metahistorical thinking in history classrooms: reflections on research and practice in England - Chapman, Arthur (Dialogos, 2016)
The history of history education, past and present, often resembles a history of contestation, in which rival and polarized understandings of the meanings of ’history’ and ’history education’ vie for dominance (Nakou and Barca, 2010). A common polarity in debates on history curricula is the opposition between ’knowledge’ and ’skill’, an opposition that has had considerable currency in recent curriculum reform processes in England which have emphasised ’core knowledge’ (DfE, 2013). Drawing on examples of classroom practice (Chapman, 2003; Woodcock, 2005; Buxton, 2003) and on systematic research and theorizing (Shemilt, 1983; Lee and Shemilt, 2009) this paper aims to destabilize such binary talk and to explore the ways in which ’first order’ knowledge and understanding about the past and ’second order’ or metahistorical knowledge and understanding of how the discipline of history works are both logically inter-related and inseparable in practical terms. The notion of historical ’enquiry’ (Counsell, 2011) is explored as a pedagogic tool for the simultaneous development of these inter-related dimensions of historical thinking.